Peran Bimbingan Keagamaan terhadap Santri Rehabilitasi di IPWL YPI Nurul Ichsan Al Islami: Bimbingan, Keagamaan, Santri Rehabilitasi, IPWL YPI Nurul Ichsan Al Islami - Ahmad Fikri Maulana (Program Studi Bimbingan Konseling Islam Fakultas Dakwah Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2021)
The purpose of this study was to determine the Spiritual behavior of the Drug Rehabilitation Santri. This research is qualitative with a descriptive approach, namely interviews and observations. The results of the study can also tell that the implementation of the Rehabilitation of Drug Santri can also be in the form of behavior patterns by providing guidance and counseling on their spiritual aspects which include aspects of Worship Practice which they have fully lived as Drug Rehabilitation Santri. Based on the results of interviews and observations, there are changes in lifestyle and mental patterns from patients who were previously lazy to become responsible individuals and pay attention to time discipline